Socio-Economic Status and Satisfaction with Service Delivery among Students in Federal Universities in South Nigeria - Okon, James; Akpoiroro, Dr Roseline M. (Advances in Social Sciences Research Journal, 2015)
The study was designed to investigate the level of students’ satisfaction with service delivery in federal Universities in South-South geopolitical zone of Nigeria on the basis of their socio-economic status. To carry out the study, the hypotheses was formulated and literature reviewed. Using the stratified random sampling technique 1,700 students out of a population of 70,808 formed the study’s sample. They were Years One, Two, Three, and Four regular undergraduate students of the 2008/2009 to 2011/2012 academic years in federal universities in south-south Nigeria. Data collected for this study was obtained through a face-validated Students’ Satisfaction with Service Delivery Questionnaire (SSSDQ) with a test-retest reliability estimate of 71 to 83. The instrument was administered to the 1,700 respondents, but only 1,450 copies were properly filled and used to assess the students’ satisfaction with service delivery in their universities based on their socio-economic status. Data collected was analyzed using descriptive statistics and a one-way analysis of variance (ANOVA). The major findings was that student’s socio-economic status significantly influenced their satisfaction with educational, library , medical, security, transport, hotel, and ICT services. Based on the findings, it was recommended that the quality of services rendered to students should constantly be monitored and upgraded to meet up with their satisfaction across socio-economic statuses. Key words: Socio-economic status, services, students’ satisfaction